High prevalence of multidrug resistant and extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolated from urinary tract infections in the West region, Cameroon - Solomon Bayaba; Raspail Carrel Founou; Flaurant Thibau Tchouangueu; Brice Davy Dimani; Lethicia Danaëlle Mafo; Omer Aurelle Nkengkana; Luria Leslie Founou; Michel Noubom (BMC Infectious Diseases)
Abstract Background Antimicrobial resistance remains a worldwide health problem with serious societal and economical repercussions. Multidrug resistant and Extended-Spectrum β-Lactamase producing-Enterobacterales (ESBL-E) are pathogens of critical public health priority that urgently require the research and development of new drugs. This study aims to determine the prevalence and characterize the genes conferring resistance to β-lactams among Escherichia coli and Klebsiella pneumoniae isolated from patients with urinary tract infections (UTIs) in the West region, Cameroon. Methods A cross-sectional study was conducted among two healthcare facilities during a four-month period from February to May, 2023. All mid-stream urine samples were collected from UTIs patients. The Escherichia coli and K. pneumoniae strains were identified using Enterosystem 18R kit following the manufacturer’s instructions. The antimicrobial susceptibility test (AST) was performed using the Kirby-Bauer disk diffusion method. The screening of ESBL production was done using ESBL ChromAgar medium combined with the double-disk synergy test (DDT). Antimicrobial resistance genes were detected using polymerase chain methods. The data analysis was performed using Excel 2016 and IBM SPSS version 20. Results A total of 215 urine samples were collected and analyzed during the study period. A 31.62% (68/215) prevalence of Enterobacterales was detected with prevalence of 79.41% (54/68) and 14.70% (10/68) for Escherichia coli and Klebsiella pneumoniae respectively. The overall prevalence of ESBL-Enterobacterales was 64.70% (44/68). About 82% (36/44) of isolates were MDR and high resistance level was observed for amoxicillin + clavulanic acid and ceftazidime. The resistance genes detected were bla CTX−M, and bla TEM respectively. Conclusion The findings of this study highlight the high burden of MDR and ESBL-E. coli and K. pneumoniae isolates from UTIs. The study emphasizes the necessity of routine screening and monitoring of antimicrobial resistance in healthcare facilities and community settings. It is therefore crucial to implement antimicrobial stewardship programs in the country and infection prevention and control (IPC) measures in hospital settings.